Linear correlation analysis of ammunition storage environment based on Pearson correlation analysis. Issue 1 (June 2021) - Yang, Qingxi; Kang, Qiaokun; Huang, Qingyang; Cui, Zenghui; Bai, Yu; Wei, Huanan
Abstract: The problem of the reliability of ammunition storage environment is a hot topic in the field of modern military research, and the key is to find out the main factors that affect the reliability of ammunition sensitive components. Grey relational entropy analysis method can find out the order of influencing factors, but it can't judge the influence size and correlation. Pearson analysis method can analyze linear correlation factors better. Therefore, this paper proposes that for the complex problems such as the influence factors of ammunition storage environment, Pearson correlation analysis method can be used to find out the linear correlation factors. Then the grey correlation entropy method is used to find out the other factors. It can lay the foundation for the follow-up analysis of the main factors. Through the comparison and analysis of the actual examples, it is found that the ranking of the influencing factors ranking by the two methods has high consistency. But Pearson method can find the linear correlation factors.